Penerapan Algoritma Dijkstra Dan Metode Topsis Dalam Sistem Rekomendasi Barbershop Berbasis Android - Hulu, Adil Priman Hati; Zalukhu, Anzas Ibezato (Jurnal Armada Informatika, 2025)
The rapid growth of modern barbershops in Medan City has increased user difficulties in determining the nearest location while selecting the best barbershop based on multiple service criteria. The main problems involve finding optimal routes and selecting the best alternatives based on price, service quality, style, health protocols, and distance. This study develops an Android-based barbershop recommendation system by integrating the Dijkstra algorithm for shortest path search and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method for alternative ranking. Dijkstra calculates the shortest distance from the user's location, while TOPSIS determines the best recommendation using weighted criteria. The results show that the system effectively provides the fastest routes and optimal recommendations according to user preferences, improving search efficiency and decision-making accuracy.